Emergence of cefiderocol resistance during therapy in NDM-5–producing Klebsiella pneumoniae isolates harboring siderophore receptors mutations - Deroche, Luc; Rozenholc, Albane; Arrivé, François; Martellosio, Jean-Philippe; Moal, Gwenaël Le; Thille, Arnaud W.; Barraud, Olivier; Marchand, Sandrine; Buyck, Julien M. (International journal of infectious diseases, 2025)
•Cefiderocol resistance occurred during treatment of an NDM-5 Klebsiella pneumoniae.•Simultaneous resistance emerged by two isogenic isolates with varying cirA mutations.•One isolate harbored mutations in two siderophores receptor genes (cirA and fiu).•Cefiderocol susceptibility testing remains challenging in clinical settings.•Cefiderol combination therapy should be considered on K. pneumoniae with high minimum inhibitory concentrations. Cefiderocol, a siderophore-conjugated cephalosporine, is a promising drug used to treat infection with carbapenem-resistant gram-negative bacteria. Here, we report a case of pneumonia induced by multiple gram-negative pathogens, including a carbapenem-resistant Klebsiella pneumoniae developing cefiderocol resistance within 32 days of cefiderocol therapy. Whole genome sequencing of three consecutive K. pneumoniae isolates revealed that the bacteria were isogenic and were carrying several broad-spectrum β-lactamases (blaNDM5 and blaCTX-M-15). Two isolates with elevated minimum inhibitory concentration against cefiderocol harbored mutations in genes encoding siderophore: one in the cirA gene and one in both the cirA and the fiu genes. The combination of a metallo-β-lactamase background and mutations in siderophore receptors was associated with phenotypic resistance to cefiderocol.